How VR can boost inspiration and increase donations - Rodrigues, M. B.; Loureiro, S. M. C.; Lopes, F. (15th Annual Conference of the EuroMed Academy of Business, Book proceedings, 2022)
One of the major challenges that non-profit organizations face is inspiring people to be concerned about issues seem geographically and emotionally distant. The aim of this study is to explore how Virtual Reality (VR) can boost inspiration and encourage potential donors to contribute to nonprofit fundraisings. To achieve this aim, a three group between-subjects experiment was conducted to examine how varying the degree of immersiveness of a short documentary about a remote health issue influences user reported social and spatial presence, inspiration, and donation intention. Findings reveal that perceived media richness gradually increases the user's spatial presence. Then, the positive effect of social and spatial presence on customer inspiration was tested and successfully verified. Finally, customer inspiration increases donation intention.